The Reactivity of Human and Equine Estrogen Quinones towards Purine Nucleosides - Zsolt Benedek (Symmetry, 2021)
Conjugated estrogen medicines, which are produced from the urine of pregnant mares for the purpose of menopausal hormone replacement therapy (HRT), contain the sulfate conjugates of estrone, equilin, and equilenin in varying proportions. The latter three steroid sex hormones are highly similar in molecular structure as they only differ in the degree of unsaturation of the sterane ring “B”: the cyclohexene ring in estrone (which is naturally present in both humans and horses) is replaced by more symmetrical cyclohexadiene and benzene rings in the horse-specific (“equine”) hormones equilin and equilenin, respectively. Though the structure of ring “B” has only moderate influence on the estrogenic activity desired in HRT, it might still significantly affect the reactivity in potential carcinogenic pathways. In the present theoretical study, we focus on the interaction of estrogen orthoquinones, formed upon metabolic oxidation of estrogens in breast cells with purine nucleosides. This multistep process results in a purine base loss in the DNA chain (depurination) and the formation of a “depurinating adduct” from the quinone and the base. The point mutations induced in this manner are suggested to manifest in breast cancer development in the long run. We examine six reactions between deoxyadenosine and deoxyguanosine as nucleosides and estrone-3,4-quinone, equilin-3,4-quinone, and equilenin-3,4-quinone as mutagens. We performed DFT calculations to determine the reaction mechanisms and establish a structure–reactivity relationship between the degree of unsaturation of ring “B” and the expected rate of DNA depurination. As quinones might be present in the cytosol in various protonated forms, we introduce the concept of “effective barriers” to account for the different reactivity and different concentrations of quinone derivatives. According to our results, both equine estrogens have the potential to facilitate depurination as the activation barrier of one of the elementary steps (the initial Michael addition in the case of equilenin and the rearomatization step in the case of equilin) significantly decreases compared to that of estrone. We conclude that the appearance of exogenous equine estrogen quinones due to HRT might increase the risk of depurination-induced breast cancer development compared to the exposure to endogenous estrone metabolites. Still, further studies are required to identify the rate-limiting step of depurination under intracellular conditions to reveal whether the decrease in the barriers affects the overall rate of carcinogenesis.